Deepening democracy comparative perspectives on decentralisation, co-operativism and self-managed development - Tharamangalam, Joseph; Chathukulam, Jos (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2023)
"This book examines the renewed interest and commitment that countries across the world have shown in recent decades towards adopting models of decentralizing, or "downsizing" the state, and moving towards more participatory models of government. It examines systems of decentralized development such as self-managing cooperatives from a global and comparative perspective with a focus on developing countries. Drawing on examples from Kerala and a few other states in India, as well as Cuba, Bangladesh and South Africa among other countries, the book offers critical perspectives on the positive impacts of these experiments and the promises these offer for the future. It discusses the challenges of implementing these models, how well these work in coordination with the civil society and the state, issues of transparency and democratic oversight as well as corruption and capture of power due to entrenched structures of inequality. The volume analyses welfare and development models and self-management interventions in countering the effects of the Covid-19 pandemic. It also looks at the merits and demerits of decentralization in countering the global socioeconomic and environmental crisis and the rise of authoritarian populism in many countries. The book will be of interest to students and researchers of development studies, political science, business, community development, social justice as well as of cooperative management programs. It will also appeal to students of political economy as well as development professionals, think tanks and policy makers"--Provided by publisher.
Experiments in deepening democracy through decentralized governance : an overview / Joseph Tharamangalam and Jos Chathukulam -- Embedded democracy / Patrick Heller -- Socialist construction and commoning / Cliff DuRand -- Thinking beyond capitalism / Errol Sharpe -- COVID-19 context in India and working towards alternative paradigms / M.A. Oommen -- Citizenship and social suffering in the context of COVID-19 / P. Sanal Mohan -- Democracy and capitalism in the time of COVID-19 / Henry Veltmeyer -- The roles of NGOs, state and for-profit agencies in improving the maternal and child sector in Bangladesh : towards a division of labour / Ahmed Tareq Rashid -- Governance, welfare-based development and COVID-19 : Sweden and Kerala in comparative perspective / Olle Tornquist -- The cure remains a symptom : sub-national government, democracy and development in South Africa / Steven Friedman -- Reorienting people's planning in Kerala / K.N. Harilal -- The capacity conundrum in decentralization and local governance : how Kerala tackles it / Joy Elamon and Sukanya K.U. -- Employment creation at a decentralized level through the construction of niche structures and promotion of self-organization / Sunil Ray -- From agricultural co-operatives to farmer producing companies : analysing the transition of co-operativism in India / K. Gireesan -- Co-operativism to manage COVID-19 / Abhilash Babu and Sabu Thomas -- Cuba's experiments with cooperativsm and solidarity economies : a move towards 21st century socialism / Joseph Tharamangalam -- Lessons and non -lessons / Joseph Tharamangalam and Jos Chathukulam.
Includes bibliographical references and index.
Keywords: Decentralization in government -- Developing countries; Cooperative societies -- Developing countries; Economic development projects -- Developing countries; Community development -- Developing countries; COVID-19 Pandemic, 2020- -- Social aspects -- Developing countries; Decentralization in government -- Developing countries. -- Case studies; Cooperative societies -- Developing countries -- Case studies; Economic development projects -- Developing countries -- Case studies; Community development -- Developing countries -- Case studies; COVID-19 Pandemic, 2020- -- Social aspects -- Developing countries -- Case studies